2014
DOI: 10.1039/c4ee00465e
|View full text |Cite
|
Sign up to set email alerts
|

Na0.67Mn1−xMgxO2 (0 ≤ x ≤ 0.2): a high capacity cathode for sodium-ion batteries

Abstract: Earth-abundant Na0.67[Mn1−xMgx]O2 (0 ≤ x ≤ 0.2) cathode materials with the P2 structure have been synthesized as positive electrodes for sodium-ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

39
407
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 425 publications
(448 citation statements)
references
References 24 publications
39
407
1
1
Order By: Relevance
“…[13][14][15][16] The reversibility of the deintercalation process in the P2 polymorph is enhanced by Mg doping. 17 Solid solutions of Mn and Fe, Na x [Mn 1-y Fe y ]O 2 , adopting either O3 or P2 structures, have also been investigated. 10,18 Polyoxyanion compounds, particularly phosphates, are receiving considerable attention as alternative cathodes for rechargeable lithium and sodium batteries.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] The reversibility of the deintercalation process in the P2 polymorph is enhanced by Mg doping. 17 Solid solutions of Mn and Fe, Na x [Mn 1-y Fe y ]O 2 , adopting either O3 or P2 structures, have also been investigated. 10,18 Polyoxyanion compounds, particularly phosphates, are receiving considerable attention as alternative cathodes for rechargeable lithium and sodium batteries.…”
Section: Introductionmentioning
confidence: 99%
“…• C. 12 The lifting and restoration of Jahn-Teller distortions, as the material is charged and discharged and the Mn oxidation state fluctuates between +3 and +4, induces a complicated sequence of electronic and structural processes evidenced by the large number electrochemical plateaus on the charge/discharge curve, as shown in Figure 6.…”
mentioning
confidence: 99%
“…On the other hand, an experimental study by Lei et al explored the Na x CoO 2 synthesis phase diagram. Na x MO 2 compounds are typically prepared via solid-state synthesis, 8,57 or a solution-state co-precipitation method, 9,12 with calcination temperatures ranging from 500 to 1000…”
mentioning
confidence: 99%
“…Unlike A x CoO 2 systems, the physical properties of A x MnO 2 have yet to be clarified, although Na x MnO 2 has recently been proposed as a new candidate for the cathode active material in Na-ion batteries [39][40][41] because Mn (Clarke number: 0.09) is more abundant than Co (Clarke number: 0.004). At least two crystallographic phases of NaMnO 2 are known; low-temperature α-NaMnO 2 [39,42] has an O3 layered structure with monoclinic symmetry and high-temperature β-NaMnO 2 [40] has a Pmnm structure with orthorhombic symmetry.…”
Section: Na ≈2/3 Mno 2 Epitaxial Filmmentioning
confidence: 99%
“…It should be noted that the crystal symmetry of Na x MnO 2 strongly depends on x. The low-temperature phase Na 0.67 MnO 2 [41,43] has a P2 layered structure with hexagonal symmetry. Recently, Billaud et al [41] reported that Na 0.67 MnO 2 with a P2 structure exhibits a high capacity of 175 mA h g −1 with a good capacity retention.…”
Section: Na ≈2/3 Mno 2 Epitaxial Filmmentioning
confidence: 99%